The Pan London Emergency Cardiac Surgery service blueprint. Issue 8 (29th June 2020) - Fudulu, Daniel Paul; Angelini, Gianni Davide; Vohra, Hunaid
Abstract: The authors share their experience of managing the cardiac surgery services across London during the challenging Covid‐19 pandemic. The Pan London Emergency Cardiac Surgery Service model could serve as a blueprint to design policies applicable to other surgical specialities and parts of the UK and worldwide.